Hematological parameters of blue-headed macaw Primolius couloni L. (Psittacidae) in captivity - Solari, Giovanna (2011)
The Blue-headed macaw (Primolius couloni) is considered a New World endangered parrot. Blood samples were collected from 13 captive blue-headed macaws (7 male, 6 female) housed in the Las Leyendas Zoological Park in Lima, Peru to establish hematologic reference values. Mean values for erythrocytes and leukocytes were 2608 x 103/ml and 10.11 x 103/ml respectively; hematocrit was 50.15% and mean corpuscular volume was 200 fl. The differential leukocyte count showed 64.7 and 25.3% of heterophils and leukocytes respectively. The largest and smallest diameter of erythrocytes was 11.3 and 7.0 μm respectively. Baseline hematologic ranges were established and can be used as reference values for this species.